Optimal sensor placement for nonlinear dynamic response prediction updating of civil engineering structures - Choo, Kian Tatt (2019)
The objective of this final year project is to optimize the locations for sensors’ placement which function to collect data of buildings in terms of their structural properties. The collected data will be used for further prediction of real life cases such as earthquakes. The more accurate the collected data, the more effective in updating the model structures. Furthermore, the data could be used for analysing structural conditions, especially deterioration and damage, also predicting the response of the structure, for instance, its durability and life cycle sustainability. A statistical approach is being adopted to compute uncertainties which may be arouse from model parameters. The method called ‘Bayesian’ statistical methodology could be applied to estimate a range of errors resulting from uncertainties and hence providing a significant level of confidence. In addition, information entropy is being used to optimize the sensors’ location by computing the least errors from the combinations. In this project, focus will be on a five-storey buildings which consists of five degree of freedom for uncertainties modelling and analysing purposes.